Mechanistic Impacts of a Scale‐Aware Convection Scheme on Typhoon Intensity: Diagnostics From Minimum Sea‐Level Pressure - Yanjie Liu; Xiaocong Wang; Yimin Liu; Hao Miao; Xuesong Zhu; Wei Huang; Yaxin Zhao; Kai Wang (Atmospheric Science Letters)
ABSTRACT This study investigates the impact of a scale‐aware convective parameterization scheme (CPS) on the simulation of typhoon track and intensity through a series of experiments using the Global‐to‐Regional Integrated Forecast SysTem (GRIST) model. The results of four typhoon cases show the scale‐aware CPS generally reduces the track error by about 15 km and the intensity error by about 10% compared to the default CPS. By analyzing the budget equation of surface pressure tendency, we found the surface pressure fall due to CPS heating is about 0.6 hPa h−1 weaker when the scale‐aware CPS is used. This is, however, compensated by enhanced microphysics heating, which more than offsets the reduction in CPS and yields a net pressure depression of about 1 hPa h−1. In fact, when parameterized convection is suppressed, the microphysics process takes up the convective instability left over by CPS and stimulates even stronger diabatic heating by 13.8%. The increased microphysics precipitation, along with the intensified grid‐scale ascending, further validates the assertion. The results of this study demonstrate the benefits of scale‐aware CPS on typhoon modeling.